Intercepting Premalignant, Preinvasive Breast Lesions Through Vaccination - Zachariah, Nadia Nocera; Basu, Amrita; Gautam, Namrata; Ramamoorthi, Ganesan; Kodumudi, Krithika N.; Kumar, Nagi B.; Loftus, Loretta; Czerniecki, Brian J. (Frontiers in Immunology, 2021)
Breast cancer (BC) prevention remains the ultimate cost-effective method to reduce the global burden of invasive breast cancer (IBC). To date, surgery and chemoprevention remain the main risk reducing modalities for those with hereditary cancer syndromes, as well as high risk non-hereditary breast lesions such as ADH, ALH or LCIS. Ductal carcinoma in situ (DCIS) is a preinvasive malignant lesion of the breast that closely mirrors IBC, and if left untreated, develops into IBC in up to 50% of lesions. Certain high-risk patients with DCIS may have a 25% risk of developing recurrent DCIS or IBC, even after surgical resection. The development of breast cancer elicits a strong immune response, which brings to prominence the numerous advantages associated with immune-based cancer prevention over drug-based chemoprevention, supported by the success of dendritic cell vaccines targeting HER2 expressing BC. Vaccination against BC to prevent or interrupt the process of BC development remains elusive but is a viable option. Vaccination to intercept preinvasive or premalignant breast conditions may be possible by interrupting the expression pattern of various oncodrivers. Growth factors may also function as potential immune targets to prevent breast cancer progression. Furthermore, neoantigens also serve as an effective target for interception by virtue of strong immunogenicity. It is noteworthy that the immune response also needs to be strong enough to result in target lesion elimination to avoid immunoediting as it may occur in IBC arising from DCIS. Overall, if the issue of vaccine targets can be solved by interrupting premalignant lesions, there is a potential to prevent the development of IBC.